SINERGI EKUITAS, LOYALITAS, MARCOM DALAM MEREK - Endro Tri Susanto (DeKaVe, 2014)
Creating and building a brand requires a long effort to bring forth. Brand that has built up andestablished businesses need to always be present in the hearts of the audience. The retention of the brand inthe minds of audiences require stratgei that consumers generally do not turn to other brands. Attempt toanswer the question of the building equity and customer loyalty to a brand is a necessity.Keywords: Brand Equity, Loyalty, Marketing Communication.